Perkembangan Kesenian Pendalungan di Kota Probolinggo Jawa Timur Tahun 1984-2018 - Wulansari, Dini Eka; Wirawan, A.A Bagus; Asmariati, A.A Inten (Humanis, 2019)
This study has discussed about the development of traditional art in Probolinggo or its called Pendalungan art in 1984-2018. Traditional art from Probolinggo, which  not widely known by the people has experienced revival through several periods of years which are supported by social community until nowadays. The formulation of the problems of the study are, (1) How are the process of developing Pendalungan art in Probolinggo? (2) What are supporting factors for the development of Pendalungan art in Probolinggo? (3) What are the implications of the development of Pendalungan art in Probolinggo ?. This study used cultural history method, and historical theory of Ida Bagus Sidemen and social science theory namely Rhole Teory by Dwi Narwoko and Bagong Suyanto were applied.The results of this study revealed that there were several roles carried out in the community elements in developing the traditional art in Probolinggo to find and preserve the identity of Probolinggo art in the midst of other arts in this area. Along the time, Pendalungan Arts finally has found the lines, namely Pendalungan Probolinggoan which consists of various kinds of art.